Evolution of Food Protein-Induced Enterocolitis Syndrome (FPIES) Index Trigger Foods and Subsequent Reactions After Initial Diagnosis - Hua, Alexandra; El-Zataari, Mohamad; Hudson, Elizabeth; Sanders, Georgiana M; Schuler, 4th, Charles F (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2023)
Food protein-induced enterocolitis syndrome (FPIES) is a non-IgE-mediated food allergy treated by trigger food avoidance and supportive care. Whether the prevalence of different trigger foods is changing with evolving food introduction patterns is unknown. The rate and nature of subsequent reactions after initial diagnosis have not been fully studied. We sought to characterize how trigger foods have changed over time and investigate the nature of subsequent reactions after initial diagnosis. We collected data regarding patients' FPIES reactions from 347 patients seen in the University of Michigan Allergy and Immunology clinic for FPIES from 2010 to 2022. Inclusion criteria consisted of pediatric patients diagnosed with FPIES by an allergist based on international consensus guidelines. Most foods including less commonly cited FPIES triggers increased in frequency over time. The most common index trigger was oat. A total of 32.9% (114 of 347) patients experienced a subsequent reaction after education on trigger avoidance and safe home introduction of new foods, with 34.2% (41 of 120) of subsequent reactions to new triggers at home and 45% (54 of 120) to known triggers at home. Of patients reacting subsequently, 28% (32 of 114) experienced a subsequent reaction necessitating an emergency department visit. The most common new subsequent reaction triggers were egg and potato, whereas peanut most commonly triggered reactions on oral food challenge. The risk profile of FPIES triggers may be evolving over time, though high-risk FPIES foods remain common. The subsequent reaction rate after counseling indicates that home food introduction poses risk. This study highlights the need for improved safety of new food introduction and/or prediction methods for FPIES to help prevent potentially dangerous home FPIES reactions.